1990
DOI: 10.1080/00173139009429979
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between fungal airspore concentration at two different sites in the South of Sardinia

Abstract: The occu-mence of airborne fungi at an urban coastal site w s compared with that at a rural inland site in the South of Sardinia. Spore concentrations at the two sites differed markedly with lower'concentrations at the urban site but the spore types found were similar. The general trend of the fungal airspores \as also very similar at both sites as a result of the similar climatic conditions. Mould spore concentrations were greatest in late spring (May-June) and autumn (October-November) with a decrease during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…), Goretti et al (I.c. ) and Palmas and Cosentino (1990), who at the same stations in Manahattan, recorded the very same results, at present under study.…”
Section: Methodssupporting
confidence: 88%
“…), Goretti et al (I.c. ) and Palmas and Cosentino (1990), who at the same stations in Manahattan, recorded the very same results, at present under study.…”
Section: Methodssupporting
confidence: 88%
“…The release of Cladosporium spores is facilitated by dry, windy conditions since it is considered a member of the "dry airspora". This observation is supported by the studies of Palmas and Cosentino (1990) who found an inverse relationship between relative humidity and Cladosporium spore counts in Sardinia, Italy; and of Ho et al (1995) who reported that high counts of this fungus in Malaysia were recorded together with low rainfall and relative humidity, and high day temperatures. In this study, there was a weak but significant inverse correlation between precipitation and Cladosporium at Ken Ridge.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, there was a weak but significant inverse correlation between precipitation and Cladosporium at Ken Ridge. Such an inverse correlation had been reported by Hyde and Williams (1953), Palmas and Cosentino (1990) and Hjelmroos (1993). However, other workers have observed a direct relationship between counts of Cladosporium and rainfall.…”
Section: Discussionmentioning
confidence: 62%
“…There are several previous reports based on the comparative study of airborne fungal spore concentrations between rural-urban or coastal-inland areas (Palmas & Cosentino 1990, Waisel et al 1997, Mitakakis, Clift & McGee 2001, Corden, Millington & Mullins 2003. This study consider ecologically or geographically different areas, and also aims to chart variations in annual, seasonal and hourly distributions of Cladosporium cladosporioides, Cladosporium herbarum and Alternaria spp.…”
Section: Introductionmentioning
confidence: 99%